FEATURES OF LIPOPEROXIDATION AND MORPHOLOGICAL CHANGES OF THE LUNGS IN EXPERIMENTAL DIABETES MELLITUS - Zaiats, L.M.; Fedorchenko, Yu.V. (World of Medicine and Biology, 2022)
In recent decades, diabetes has become one of the most significant medical and social problems. The prevalence and incidence of diabetes have increased dramatically in the last few years. The experiments were performed on white male rats with streptozotocin-induced diabetes. Biochemical analysis has shown that in the conditions of experimental diabetes there is an intensification of lipid peroxidation processes throughout the study period, as evidenced by a significant increase in the content of active products of thiobarbituric acid (p